Adult Continuing Education in Health - Fani Pegiou; Lambrini Kourkouta; Konstantinos Koukourikos; Christos Iliadis; Theodora Thomopoulou and Areti Tsaloglidou (Professor Despina Sapountzi-Krepia, 2024)
Adult Continuing Education in Health